Administration of justice and applicability of Deterrent theory of law in relation to Kautilya’s Arthashastra (Bhartiya Knowledge Systems, 2024)
The Kautilya’s Arthashastra addresses the economic aspects of statehood in the colossal Mauryan Empire which covers the aspects of Law and Justice. The Arthashastra converges juristic approaches to the modern legal jurisprudence, which the latter alienates the legal principles that Kautilya tables in Arthashastra. The juristic principles propounded by Kautilya in the Arthashastra collide with the modern system of jurisprudence and present a similar theory while remaining correlated despite being from a different time period. The article provides a bird eye view of the concepts that Arthashastra provides, which is drafted within significant principles in modern jurisprudence, such as Deterrent Theory of Punishment, Rule of Law and stated through various laws of precedence as pronounced by Courts in India. The proposed outcome is to create relevance of Arthashastra as a significant legal jurisprudence in application exploring beyond its popular economic aspects and giving insights into it.